Answer:
f(g(-3)) = -11
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Algebra I
- Functions
- Function Notation
- Composite Functions
Explanation:
Step 1: Define
Identify
f(x) = 2x - 1
g(x) = 2x + 1
x = -3
Step 2: Evaluate
- Substitute in x: f(g(-3))
- Substitute in x [Function g(x)]: g(-3) = 2(-3) + 1
- Multiply: g(-3) = -6 + 1
- Add: g(-3) = -5
- Rewrite: f(-5)
- Substitute in x [Function f(x)]: f(-5) = 2(-5) - 1
- Multiply: f(-5) = -10 - 1
- Subtract: f(-5) = -11